4-in-1 Dictionary: An Intervention for Science 7 Learning - Mariane Capellan Ogaya (Future Science / FSH-PH Publications, 2026)
This study, titled “4-in-1 Dictionary: An Intervention for Science 7 Learning”, was conducted to investigate the effectiveness of a 4-in-1 dictionary as a learning intervention to enhance science concept comprehension among Grade 7 students of Centro Integrated School. It sought to answer the following questions: What is the performance level of the students before and after the intervention? Is there a significant difference between the mean pretest and mean posttest performance of the experimental group? And what are the experiences of the learners in the utilization of the intervention? Qualitative and quantitative methods were employed in this study. It utilized pre and post-tests, and a written interview. Twenty-two (22) students served as the respondents of the study. Pre and post-tests were utilized to determine the performance level of the students before and after the intervention and its significant differences. A written interview was conducted to get their experiences in the utilization of the intervention. Paired t-test and percentage are the methods that are used in the research. Thematic analysis was the qualitative research method. The study findings suggest that there was a significant difference in the posttest mean score and the pretest mean score, thus 4 in 1 dictionary is effective on science concepts. According to students’ qualitative data, they felt towards the intervention which demonstrates the usefulness of intervention as a pedagogical for teaching science.